A stochastic model of TCP - Eitan Altman (Computer communication review.)
We present a technique for identifying repetitive information transfers and use it to analyze the redundancy of network traffic. Our insight is that dynamic content, streaming media and other traffic that is not caught by today's Web caches is nonetheless likely to derive from similar information. We have therefore adapted similarity detection techniques to the problem of designing a system to eliminate redundant transfers. We identify repeated byte ranges between packets to avoid retransmitting the redundant data.